Motivasi Belajar Pendidikan Jasmani: Penerapan Teknik Memotivasi Teaching by Invitation pada Pendekatan Teknis - Nur, Lutfi; Malik, Arief Abdul (Prodi PGSD Penjas FPOK UPI, 2020)
In physical education learning activities, motivational factors become one of the key activeness of students in moving. This study aims to determine the effectiveness of a technical approach using techniques to motivate teaching by invitation to learning motivation in physical education learning. This research is a quasi-experimental study involving the dick group consisting of 25 students (12 male and 13 female) and the experimental group consisting of 23 students (11 male and 12 female). The instrument used was a motivation questionnaire with a reliability score of alpha Cronbah 0.896. The results showed that there were significant differences between the experimental and control groups with a t value of 3.022 and a significance of 0.004 0.05. The technique of motivating teaching by invitation effectively can increase student motivation in participating in physical education learning.Â AbstrakPada kegiatan pembelajaran pendidikan jasmani (penjas), faktor motivasi menjadi salah satu kunci keaktifan siswa dalam bergerak. Penelitian ini bertujuan untuk mengetahui efektivitas pendekatan teknis menggunakan teknik memotivasi teaching by invitation terhadap motivasi belajar dalam pembelajaran penjas. Penelitian ini merupakan penelitian kuasi eksperimen dengan melibatkan kelompok kontrol sebanyak 25 siswa (12 laki-laki dan 13 perempuan) dan kelompok eksperimen terdiri dari 23 siswa (11 laki-laki dan 12 perempuan). Instrumen yang digunakan adalah angket motivasi dengan reliabilitas skor alpha Cronbah 0.896. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol dengan nilai t hitung 3,022 dan signifikansi 0,004 0,05. Teknik memotivasi teaching by invitation secara efektif mampu meningkatkan motivasi siswa dalam mengikuti pembelajaran penjas.